Research of the Movement Law of Output Mechanism with Shaking Block Chute Type Small Tooth Number Difference - Li Wei; Cui Jiankun (Jixie chuandong)
A new type of output mechanism with shaking block chute type small tooth number difference is proposed,and the motion analysis of the transmission pin and the output shaft is carried out. Then through the software establishment three-dimensional model,the movement simulation analysis of the reducer is carried out.The characteristics of the output movement is studied. By changing the distance between the drive pin and the outer gear center and other parameters,the smoothness of the output movement is improved.